(3GdeYjGQ dbQGFM GdfXGQ aj TQM MbGFb GdCOdI GdabgjI hJbQjQ GdbhGYO GdbjGSjIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3CMeO Hf SdjeGf s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdOjGf , GdeJcHQ GdefGf CeG HYO , aEf Gdgd deG habfi dEJeGe cJGH GdMGhi hcGf bO aQZ Ydi Whd CHhGH hcKQI eSGFd QHeG UYH JfGhdgG hbO QJHJg Ydi UOQ hebeOeg hYTQI CUhd s
(3BNQgG (B:s
(3aEPG JYGQV YdJGf , hcGfJ EMOGgeG jQO ajgG GdaQY Edi eGgh ef LfSg hgPG bhd GdCcKQ ef CUMGH GdTGaYi hHJeGeg Je GdcdGe ai GdcJGH s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdahGJM HGdSejc YdjgG Jedc HGSe Ydi Hf eMeO Hf GdeQJVis
(3ChQGbgG eVWQHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdabg GdESdGejs